Characterization of Micro/Mesoporous Materials by Physisorption: Concepts and Case Studies - Sotomayor, Francisco; Cychosz, Katie A.; Thommes, Matthias (Accounts of Materials & Surface Research, 2018)
Utilizing case studies of selected materials, including hierarchical zeolites, controlled pore glasses, and mesoporous carbons, we demonstrate that physisorption analysis is a valuable tool in the structural characterization of a broad range of nanoporous materials. In conjunction with the selected case studies, we illustrate how application of advanced methodologies allows for the determination of surface areas, pore volumes, and pore size distributions over the complete range of micro-, meso-, and even narrow macropores. We discuss important aspects of state-of-the-art gas adsorption methodologies, in line with recent recommendations by the IUPAC. Rather than serving as a broad review of gas adsorption literature, this paper highlights basic concepts and resources for understanding gas adsorption characterization in a modern context and offers practical guidance for users of gas adsorption instruments, especially those in industrial settings.